KEKUATAN PEMBUATAN AKTA OTENTIK YANG MEMBATALKAN AKTA NOTARIS (STUDI KASUS PUTUSAN PENGADILAN NEGERI MEDAN NOMOR 347/PDT.G/2012/PN-MDN) - YANTI MALA (PREMISE LAW JURNAL, 2015)
The authenticity of a Notary is found in Article 1, paragraph 1 of Notarial Act No. 2/2014 in which a Notary is regarded as a “ public official empowered to draw up authentic deeds and other authorities as it is intended by this law/ or by other laws” so that the deeds drawn up by a Notary is authentic. Therefore, the authentic deeds can be cancelled when they are physically, materially, and formally legally defective. In this case, the research on the Evidentiary Value of Drawing up Authentic Deeds which Cancels Notarial Deeds (A Case Study on the Verdict of Medan District Court No. 347/PDT.G/2012/PN-MDN) needs to be conducted. The conclusion of the research was that a Notary’s attempt to forestall the breach of the parties concerned in Notarial deeds was by performing his obligation as a Notary as it is stipulated in Notarial Act No. 2/2014 and notarial Code of Ethics. In practice, a Notary has to read the content of the deed and explain to the person appearing about the content before some witnesses, either from the Notary himself or from the person appearing, provide a special pages for finger prints as evidence, in case of any dispute in the future. A Notary’s attempt to deter civil sanction on notarial deeds which have evidentiary value as underhanded deeds and the cancelation by law is by proving that the deeds have complete evidentiary value and do not violate Article 84 of Notarial Act. He has to fight and explain that the deeds are made upon the request of the parties concerned according to the procedures. If he can prove it from the physical, formal, and material viewpoints, he can counter sue in order to defend his rights and obligation in performing his profession. Keywords:Notary, Drawing up Authentic Deeds, Canceling Authentic Deeds